Association of ideal cardiovascular health at age 50 with incidence of dementia: 25 year follow-up of Whitehall II cohort study. (31st July 2019) - Sabia, Séverine; Fayosse, Aurore; Dumurgier, Julien; Schnitzler, Alexis; Empana, Jean-Philippe; Ebmeier, Klaus P; Dugravot, Aline; Kivimäki, Mika; Singh-Manoux, Archana
Abstract: Objectives: To examine the association between the Life Simple 7 cardiovascular health score at age 50 and incidence of dementia. Design: Prospective cohort study. Setting: Civil service departments in London (Whitehall II study; study inception 1985-88). Participants: 7899 participants with data on the cardiovascular health score at age 50. Exposures: The cardiovascular health score included four behavioural (smoking, diet, physical activity, body mass index) and three biological (fasting glucose, blood cholesterol, blood pressure) metrics, coded on a three point scale (0, 1, 2). The cardiovascular health score was the sum of seven metrics (score range 0-14) and was categorised into poor (scores 0-6), intermediate (7-11), and optimal (12-14) cardiovascular health. Main outcome measure: Incident dementia, identified through linkage to hospital, mental health services, and mortality registers until 2017. Results: 347 incident cases of dementia were recorded over a median follow-up of 24.7 years. Compared with an incidence rate of dementia of 3.2 (95% confidence interval 2.5 to 4.0) per 1000 person years among the group with poor cardiovascular health, the absolute rate differences per 1000 person years were −1.5 (95% confidence interval −2.3 to −0.7) for the group with intermediate cardiovascular health and −1.9 (−2.8 to −1.1) for the group with optimal cardiovascular health. Higher cardiovascular health score was associated with a lower risk of dementia (hazard ratio 0.89 (0.85 to 0.95) per 1 point increment in the cardiovascular health score). Similar associations with dementia were observed for the behavioural and biological subscales (hazard ratios per 1 point increment in the subscores 0.87 (0.81 to 0.93) and 0.91 (0.83 to 1.00), respectively). The association between cardiovascular health at age 50 and dementia was also seen in people who remained free of cardiovascular disease over the follow-up (hazard ratio 0.89 (0.84 to 0.95) per 1 point increment in the cardiovascular health score). Conclusion: Adherence to the Life Simple 7 ideal cardiovascular health recommendations in midlife was associated with a lower risk of dementia later in life.